Polarization‐Dependent Photocurrent of Black Phosphorus/Rhenium Disulfide Heterojunctions. Issue 22 (19th September 2018) - Li, Xiao‐Kuan; Gao, Xiao‐Guang; Su, Bao‐Wang; Xin, Wei; Huang, Kai‐Xuan; Jiang, Xiao‐Qiang; Liu, Zhi‐Bo; Tian, Jian‐Guo
Abstract: Van der Waals (vdW) heterojunctions of 2D layered materials possess excellent interface quality without the constraint of lattice mismatch, which enables the application of nanomaterials in electronic and optoelectronic devices. The anisotropy of 2D materials however, also plays an important role in the stacking process of vdW heterojunction. Black phosphorus (BP) and rhenium disulfide (ReS2 ), as two strong anisotropic 2D materials, have intrinsic in‐plane anisotropic properties that can be used in polarization‐sensitive photoelectric devices. Herein, two types of BP/ReS2 heterojunctions are stacked by controlling their crystal orientation, with the armchair (AC) direction of BP parallel to the b ‐axis of ReS2 (ABJ) and zigzag (ZZ) direction of BP parallel to the b ‐axis of ReS2 (ZBJ). ABJ exhibits stronger polarization‐dependent photocurrent with a polarized photocurrent ratio of 31, when polarized light is illuminated along the AC and ZZ directions. Our results suggest that this heterojunction has potential application in polarization‐dependent optoelectronic detection. Abstract : Two types of BP/ReS2 heterojunctions are stacked by controlling their crystal orientation. The orientation‐induced heterojunction with the direction of AC parallel to the b ‐axis of ReS2 is called ABJ, and with direction of ZZ parallel to the b ‐axis is called ZBJ. ABJ exhibits a stronger polarization‐dependent photocurrent with a polarized photocurrent ratio up to 31.